The benefit surcharge and its labyrinth - Delgado Ruiz, Jose (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
A complex aroma has the surcharge of Social Security benefits, enclosed in its own nature and in a play on words that does not cease. The employer’s duty of safety is an elastic concept that adjusts to the many factors involved in the production of the damage and undergoes serious alterations when mixed with the recklessness of another worker or a third party outside the work environment. In order to undo the entanglement of the figure, it would be necessary to separate its infringing origin from the true face that it presents as a singular benefit aimed at preventing and compensating accidents at work and occupational diseases.
Keywords: Work accident; benefit surcharge; dismissal; liability; imprudence